НАРСАЛАР ИНТЕРНЕТИ IOT ТИЗИМИДА АХБОРОТ ХАВФСИЗЛИГИГА ТАҲДИДЛАР ВА УЛАРНИНГ ТАҲЛИЛИ - Кабулов, А.В.; Ярашов, И.К.; Самандаров, Б.С. (SCIENCE and SOCIETY, 2021)
IoT technology is the key to solving research issues that need to be addressed. There are various configurations that need to be addressed in the physical part of the IoT and in the network domain. IoT automation programs have special requirements in real time, they have a high level of reliability and security in a stable environment. These requirements strengthen security and high security measures. This article discusses the security threats to environmental data that may occur at various levels of the IoT architecture, particularly in the field of ecology. Impact mitigation methods include physical solutions for sensors, data processing applications, and communication infrastructure as a result of various measurements, as well as security in IoT.